Impacto socioeconómico de los servicios financieros de la Cooperativa de Ahorro y Crédito Agrícola Junín Ltda. en sus asociados - Zambrano Mendoza, Edison Oswaldo (2025)
The research focused on evaluating the socioeconomic impact of the financial services provided by the Cooperativa de Ahorro y Crédito Agrícola Junín Ltda., with the aim of proposing improvements for its members. A mixed-methods approach was employed, combining qualitative and quantitative methodologies to achieve the established objectives. The study included field research, through data collection at the cooperative, and bibliographic research, by reviewing theoretical foundations relevant to the investigation. The applied methods included deductive, analytical-synthetic, and descriptive approaches. A simple random probabilistic sampling method was used. Surveys assessed the socioeconomic impact of financial services, and the 5W+1H matrix was applied to propose future improvement actions. The results indicated that the financial services of Cooperativa de Ahorro y Crédito Agrícola Junín Ltda. have had a positive impact on the quality of life of its members. A total of 81% of respondents reported that these services had enabled them to make improvements to their homes, enhancing their overall well-being. Additionally, 99% expressed confidence in the financial products and stated that they would use them again (p.97). However, areas for improvement were identified, such as insufficient loan amounts (28%) and difficulties in obtaining guarantees (15%). As a corrective measure, it was proposed to review loan policies to offer more adequate amounts and simplify guarantee requirements.